Structural, morphological, Raman and ac electrical properties of the multiferroic sol-gel made Bi0.8Er0.1Ba0.1Fe0.96Cr0.02Co0.02O3 material - Benali, A. (2018)
We have investigated the effect of multi-doping in A and B site of the multiferroic prepared by the Sol-gel method Bi0.8Er0.1Ba0.1Fe0.96Co0.02Cr0.02O3 (BEBFCC) on the structural, morphological and electric properties. X-Ray diffraction and Rietveld refinement confirm that the BEBFCC compound presents a rhombohedral structure with the R3C space group. The Ac electrical properties have been measured from 331 to 735 K as a function of frequency (100 kHz - 1 MHz). Debye's theory and Arrhenius relations were used to study the relaxation phenomenon. The frequency dependence of the impedance (Z”: imaginary part) reveals the existence of one relaxation peak, while the Modulus formalism shows two peaks. The presence of two contributions, related to the dielectric relaxations visible in this compound, was confirmed by the Impedance Nyquist plots. The study of the ac conductivity based on Jonsher's power law confirms that the conduction is associated to the Non-Overlapping Small Polaron Tunneling model.